THE EDUCATIONAL MODEL IN SWEDEN: DEMOCRATIC PRINCIPLES AND PERSONAL ORIENTATION - Nezhyva, Olga (Educological discourse, 2019)
The author considers the peculiarities of formation and development of the education system in Sweden. The author also shows the main factors which had a great importance in the promotion of democratic education and ways to improve it. At the same time the author analyzes peculiarities of modern development strategy of the Swedish education system, taking into account today’s democratization. Also this country has a medieval history not only of its establishment or development of their culture, but also education, which has come a long way of the recovery. It should be noted that the structure of the Swedish system more rapidly developed as a pluralistic, complex and fragmented, with its own dynamics and mechanisms that ensure homogenization / divergence and cooperation / competition. The system includes a remarkable number of institutions of varying size, profile and traditions that are now competing. All Swedish universities are under the jurisdiction of the Ministry of Education. The exception is the Swedish University of Agricultural Sciences, which is under the jurisdiction of the Ministry of Agriculture, Food and Fisheries. Thus, universities and university colleges are in direct contact with the relevant ministry. Of course, this led to the fact that Sweden is called as one of educated countries and this country has the best educational model. For the reason that the higher education system has undergone fundamental changes over the past thirty years. The emphasis has shifted from national planning for greater independence and self-responsibility for the institutions. Former collegiate structure in the organs of decision makers in higher education have been transformed into a managerial structure.